Anthropometric Analysis of the Nigerian Face: Any Conformity to the Neoclassical Canons?. Issue 7 (October 2018) - Olusanya, Adeola Adenike; Aladelusi, Timothy Olukunle; Adedokun, Babatunde
Abstract : Abstract: This study defines the facial anthropometric and aesthetic measurements in young Nigerians. This is a prospective cohort study involving facial anthropometric measurement in young adults without craniofacial abnormalities. Ten anthropometric measurements (upper facial height (tr-n), mid-facial height (n-sn), lower facial height (sn-gn), height of auricle (sa-sba) bilaterally, intercanthal width (en-en), palpebral fissure width (en-ex) bilaterally, face width (zy-zy), nose width (al-al), mouth width (ch-ch) and the interincisal distance) were determined. Proportions were compared with neoclassic cannons, published North American and Asian norms 151 individuals consisting of 50 males and 51 females with age range from 16 to 31 (23.9 + 2.49) were enrolled. Only 1% of the study population had equal facial thirds, the midface was the shortest of the facial thirds and the male gender generally had larger mean values of the facial dimensions than the female gender. About half of the participants had the lower third > upper third > middle third, the intercanthal width was equal to the nasal width in only about a tenth of the participants and less than the nasal width in majority (88.1%) of the participants and the mean interincisal distance was 51.1 (SD ± 6.997). The anthropometric measurements from this Nigerian study do not conform to the neoclassical cannons. Racially sensitive facial canons and measurements are advocated during reconstructive and aesthetic interventions in the craniofacial region.